Acidification of Cocoa Nibs using Malic Acid to Modify the Color While Preserving the Bioactive Compounds. - Febrianto, Noor Ariefandie; Novella Ramadhani, Trisnaningtyas; Taufiq Utami, Rachma (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
The occurrence of non-fermented cocoa beans in the Indonesian market is still a huge challenge that needs to be solved. Unfermented cocoa beans are considered low-quality cocoa due to their low chocolate flavor and taste, and high bitterness and astringency levels. This limits its usability in the industries. An effort to utilize unfermented cocoa beans can be made through an alternative processing method utilizing an acidification process. Malic acid was used for acidification at various concentrations (0.01, 1, 2.5, and 5%). This acid solution was used to incubate the cocoa nibs for 1,3 and 5 hours. Physicochemical characteristics such as color changes, anthocyanin content, total phenolic content, and antioxidant activity of acidified cocoa nibs were analyzed. Fourier transform infrared spectroscopy analysis was also utilized to evaluate the changes in the functional groups. The results showed that the acidification of cocoa nibs using >1% malic acid significantly altered the color of cocoa nibs from brownish-purple to reddish color. Anthocyanin and phenolic content of cocoa nibs could be preserved to more than 61 and 65%, resulting in preserved antioxidant activity (>66%). The use of 2.5% malic acid followed by incubation for 3 hours resulted in cocoa nibs with bright red color and highly-preserved bioactive compounds.